Apprendre en stage : situation de travail, interactions et participation - Souâd Denoux (Éducation et Socialisation)
Referring to the workplace learning theories and to the transmission theories, this article is interested in the civil engineering foremen training whose profession belongs to the field of the experience works. It examines the impact of the professional organization features, the role of the interactions with the tutors and the more experienced colleagues as well as the use by the trainees of the corporate resources. The analysis of interviews with trainees and trainers and the data coming from the field observations show that the links between organizational factors and trainees ’ones have a great importance. The work situations, the trainees’ interactions with their partners, and the way they turn to good account the professional context resources, under certain conditions, strongly change the direction of the workplace learning during the vocational training.